Effects of pH in Mercury Nitrate Treatment using Membrane System with Biological Pretreatment - Mohd Fadzlan, Fazlyla (Journal of Science and Technology, 2014)
Wastewater from industry containing mercury is very dangerous. Hence we need to treat the wastewater effectively to avoid its toxic effects. The usage of membrane in wastewater treatment has increased due to its ability to filtrate unwanted particle. Modification of the membrane parameters may produce better result than changing the type of membrane for filtration of mercury in wastewater. Using P.putida as the pretreatment or volatilizing agent and continue with the alternation of pH value, this technique seems to be able to remove mercury (Hg) to the minimum permitted level easily. Based on the study conducted, the pretreatment stage decreased the concentration of Hg solution from 250ppb to 8ppb. The concentration was further decreased to 0 ppb within the pH of 8 to 9, following the membrane separation. As a conclusion, pH 8 to 9 is the best pH for operating membrane to filtrate mercury wastewater since the membrane operates at neutral or base condition.